Novel numerical model to simulate water seepage through segmental gasketed joints of underwater shield tunnels considering the superimposed seepage squeezing effect - Yan, Qixiang; Zhong, Haojia; Zhang, Chuan; Zhao, Zechang; Wen, Yanxin; Wang, Ping (Underground space (Beijing), 2023)
The water leakage through segmental joint gaskets has become a major concern that adversely affects the normal serviceability of underwater shield tunnels throughout the construction and operational periods. Therefore, it is of great significance to investigate the sealing performances of the joint gaskets, which directly helps evaluate the waterproof capacity of underwater shield tunnels. To date, the numerical modeling plays an irreplaceable role in the analysis on the waterproof capacity of the joint gaskets. Nevertheless, conventional methods tend to ignore the self-sealing effect induced by the water seepage pressurization, thus failing to reveal the progressive evolution of the water infiltration process through the joint gasket. To remedy this defect, this paper proposed a novel numerical model to simulate the penetration process of the sealing gasket based on the Python language-enabled secondary programming in the ABAQUS software, which could fully consider the superimposed seepage squeezing effect. Based on the proposed model, the waterproof failure process and the dynamic contact stress of the gasket’s water seepage path subject to excessive hydraulic pressure were thoroughly investigated. Moreover, indoor tests on the waterproof capacity of the gasket were also performed to validate the proposed model. It is found that the numerical results from the developed model are consistent with the experimental results. This research will contribute to better understanding of the gaskets’ hydraulic penetration process and more accurate prediction of the maximum waterproof capacity in underwater shield tunnels.